Prosumer Data Gathering and Grid State Forecast Using Smart Grid Technology - Bagus Satrio Utomo; Arif Bramantyo, Hutama; Dwi Wibisono, Randi; Adi Nugraha, Rizky (PT Konsuli Corpora Indonesia, 2025)
The increasing global energy demand, combined with environmental concerns, has accelerated the development of smart grids as a sustainable solution. Smart grids enable bidirectional energy and information flow, allowing users to also act as energy producers—referred to as